Migrant birds disperse haemosporidian parasites and affect their transmission in avian communities. Issue 6 (6th April 2021) - de Angeli Dutra, Daniela; Filion, Antoine; Fecchio, Alan; Braga, Érika Martins; Poulin, Robert
Abstract : Migration has an important impact on the transmission of pathogens. Migratory birds disperse parasites through their routes and may consequently introduce them to new areas and hosts. Hence, haemosporidian parasites, which are among the most prevalent, diverse and important bird pathogens, are potentially dispersed when infecting migrant hosts. Further, migrant hosts could enhance local parasite prevalence and richness by transporting new parasite strains to new areas. Here, we hypothesize and aim to evaluate if 1) migratory birds spread parasite lineages along their routes, and 2) localities crossed by more migratory birds have greater prevalence and richness of haemosporidians. For the first hypothesis, we tested whether parasite lineages found 1) in both migrants and residents, and 2) only in residents, differ in their frequencies of occurrence among localities. For the second hypothesis, we tested for a relationship among localities between the overall local haemosporidian parasite richness and prevalence, and the proportion of migratory bird individuals present in a locality. We combined a dataset on 13 200 bird samples with additional data from the MalAvi database (total: 2800 sequenced parasites comprising 675 distinct lineages, from 506 host species and 156 localities) from South America, and used Bayesian multi‐level models to test our hypotheses. We demonstrate that parasites shared between resident and migratory species are the most spatially widespread, highlighting the potential of migrants to carry and transmit haemosporidians. Further, the presence of migrants in a locality was negatively related to local parasite richness, but not associated with local prevalence. Here, we confirm that migrants can contribute to parasite dispersal and visiting migrants are present in regions with lower Plasmodium prevalence. Also, we observed their presence might raise Haemoproteus community prevalence. Therefore, we demonstrate migrants enhance pathogens spread and their presence may influence parasite community transmission.